0 = x^7 + y^7 - 7axy dy/dx = ( 7x^6 - 7y ) / (7x - 7y^6) dy/dx = ( x^6 - y ) / (x - y^6) ( i entered this as my answer and i got it wrong :S)
Follow Math Help Forum on Facebook and Google+
Originally Posted by rock candy 0 = x^7 + y^7 - 7axy dy/dx = ( 7x^6 - 7y ) / (7x - 7y^6) dy/dx = ( x^6 - y ) / (x - y^6) ( i entered this as my answer and i got it wrong :S) x^7 + y^7 - 7axy = 0 7x^6 + 7y^6 dy/dx - 7ay -7axdy/dx = 0 7x^6 - 7ay =7axdy/dx - 7y^6 dy/dx 7x^6 - 7ay =(7ax - 7y^6) dy/dx dy/dx=(x^6 - ay) /(ax - y^6) ````````````````````````````````````````````` Oh My Dear! you forgot "a" :P take care next time
View Tag Cloud